2020
DOI: 10.1002/jsfa.11015
|View full text |Cite
|
Sign up to set email alerts
|

Combining high‐protein ingredients from pseudocereals and legumes for the development of fresh high‐protein hybrid pasta: enhanced nutritional profile

Abstract: BACKGROUND: The fortification of wheat-based staple foods, such as pasta, with pseudocereal and legume flours has received growing research interest in recent years. While it is associated with many challenges regarding technological and sensory quality of the products, it promises a substantial improvement of the nutritional value of pasta. However, investigations of the nutritional quality of fortified pasta often focus on the carbohydrate/starch fraction, and information on changes in protein quality is rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…Even though the incorporation of some ingredients revealed to be challenging in terms of sensory and technological quality characteristics, advances in pasta research have demonstrated different possibilities. For instance, Hoehnel et al (2020) have recently shown the benefits of wheat pasta fortification (semolina replaced at a level of ∼24%) with a mixture of protein-rich ingredients from buckwheat, fababean, and lupin and achieved an improved high-quality protein profile. As the substitution of semolina with other low FODMAP ingredients (e.g., LF grains, LF protein isolates from pulses, dietary fibers) has not been investigated to date for the production of LF pasta, studies are required on the incorporation of different ingredients and the concomitant consequences.…”
Section: Impact Of Cooking During Food Preparationmentioning
confidence: 99%
“…Even though the incorporation of some ingredients revealed to be challenging in terms of sensory and technological quality characteristics, advances in pasta research have demonstrated different possibilities. For instance, Hoehnel et al (2020) have recently shown the benefits of wheat pasta fortification (semolina replaced at a level of ∼24%) with a mixture of protein-rich ingredients from buckwheat, fababean, and lupin and achieved an improved high-quality protein profile. As the substitution of semolina with other low FODMAP ingredients (e.g., LF grains, LF protein isolates from pulses, dietary fibers) has not been investigated to date for the production of LF pasta, studies are required on the incorporation of different ingredients and the concomitant consequences.…”
Section: Impact Of Cooking During Food Preparationmentioning
confidence: 99%
“…The most desirable cooking properties of top-quality pasta include a moderate water uptake at the optimal cooking time (OCT) and a low cooking loss [Bustos et al, 2015;Cole, 1991]. Moreover, the nutritional properties of pasta have recently spurred a growing interest mainly due to the development of new, fortified products [Hoehnel et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
“…[Filip & Vidrih, 2015;Hoehnel et al, 2020]. Therefore, there have been many scientific attempts to incorporate the protein-rich ingredient into pasta formulations[Duda et al, 2019; Hoehnel et al, 2020; Raczyk et al, 2022].…”
mentioning
confidence: 99%
“…Wang et al 13 also studied the influence of functional vegetable ingredients on the nutritional quality of pasta, obtaining very promising results, such as improved nutritional value, increased antioxidant capacity and an increase in the fiber content of the pasta. Hoehnel et al 14 developed fresh hybrid protein-rich pasta using a mixture of buckwheat, fava beans and lupine (to replace wheat semolina), achieving a product with a better nutritional content and a balanced amino acid profile.…”
Section: Introductionmentioning
confidence: 99%